2012
DOI: 10.1375/twin.15.1.97
|View full text |Cite
|
Sign up to set email alerts
|

The Heritability and Genetic Correlates of Mobile Phone Use: A Twin Study of Consumer Behavior

Abstract: There has been almost no overlap between behavior genetics and consumer behavior research, despite each field's importance in understanding society. In particular, both have neglected to study genetic influences on consumer adoption and usage of new technologies — even technologies as important as the mobile phone, now used by 5.8 out of 7.0 billion people on earth. To start filling this gap, we analyzed self-reported mobile phone use, intelligence, and personality traits in two samples of Australian teenaged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(23 citation statements)
references
References 82 publications
1
20
0
1
Order By: Relevance
“…Evidence for sex differences in genetic aetiology is inconsistent across the literature on media use [811]. Where sex differences are found [8, 10], they are typically small with overlapping confidence intervals, as in the present study.…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…Evidence for sex differences in genetic aetiology is inconsistent across the literature on media use [811]. Where sex differences are found [8, 10], they are typically small with overlapping confidence intervals, as in the present study.…”
Section: Discussionmentioning
confidence: 46%
“…This development calls for an investigation of the origin of individual differences in online media use, especially as all previous studies in this area focused on clinical samples and on problematic or pathological internet use [5, 6, 810] or were based on small sample sizes [11]. …”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, one twin study concerning genetic and environmental influences on media use and communication behaviors revealed that individual differences in hours spent using the Internet in the previous 7 days were mainly (67% of the variance) due to the non-shared environmental influences, whereas the additive genetic contribution was only 10% (Kirzinger, Weber, & Johnson, 2012). Another twin study concerning the heritability of mobile phone use showed that the nonshared environmental influences on mobile phone talk and text messaging frequencies were modest to moderate, ranging from 28% to 45% (Miller, Zhu, Wright, Hansell, & Martin, 2012). The same study also showed that the additive genetic contributions to mobile phone talk and text messaging frequency ranged from 34% to 60%.…”
Section: Discussionmentioning
confidence: 99%
“…Turkheimer (2000) summarized the results of many thousands of studies in behavioral genetics in three laws, the first being that "everything is heritable." While this law may not be true in its extreme formulation, almost every aspect of usual human social behavior that has been studied with behavioral genetic data has indeed been found to have some genetic origins, including the size of social networks (Fowler et al 2009;Freese 2008;McGue and Bouchard 1998), and even mobile phone use (Miller et al 2012). Specific political party preference seems to be one of the few exceptions (Hatemi et al 2009).…”
Section: Genesmentioning
confidence: 99%